2015
DOI: 10.1136/tobaccocontrol-2015-052260
|View full text |Cite
|
Sign up to set email alerts
|

Price-related promotions for tobacco products on Twitter

Abstract: Objectives This cross-sectional study examined price-related promotions for tobacco products on Twitter. Methods Through the Twitter Firehose, we obtained access to all public tweets posted between December 6, 2012 and June 20, 2013 that contained a keyword suggesting a tobacco-related product or behavior (e.g., cigarette, vaping) in addition to a keyword suggesting a price promotion (e.g., coupon, discount). From this dataset of 155,249 tweets, we constructed a stratified sampling frame based on the price-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 7 publications
0
34
0
Order By: Relevance
“…Recent studies have investigated e-cigarettes on Twitter with the primary focus on commercial tweets 8 9. Our data collected in late 2015 added two new findings when compared with Twitter data collected in mid-2012 8.…”
Section: Summary and Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Recent studies have investigated e-cigarettes on Twitter with the primary focus on commercial tweets 8 9. Our data collected in late 2015 added two new findings when compared with Twitter data collected in mid-2012 8.…”
Section: Summary and Discussionmentioning
confidence: 75%
“…Existing studies of e-cigarettes on Twitter lacked spatial analysis of tweeters 8 9. Some studies were only able to identify longitude and latitude from less than 1% of tweets in Twitter metadata 14 15.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…732,746 ENDS are promoted heavily online 451,695 through ENDS company–sponsored advertisements 697 and users’ social media profiles, 424 with occurrences on YouTube 690,697,706,707,710,722,731,739 and Twitter. 691,713,715,725727,733,743 Youth and young adult exposure to TV advertisements for ENDS has increased since 2011. 689,735 Two RCTs 712,720 and four cross-sectional studies 403,629,723,741 have shown that tobacco marketing exposure may promote ENDS uptake.…”
Section: Evidence Synthesismentioning
confidence: 99%
“…Previous studies have demonstrated that Twitter is a popular venue where substance use behaviors are openly discussed, and researchers have accordingly used Twitter data for substance use epidemiology research (Alvaro et al, 2015; Cavazos-Rehg et al, 2015a; Cole-Lewis et al, 2015; Hanson et al, 2013; Jo et al, 2015; Lamy et al, 2016; Myslin et al, 2013; Thompson et al, 2015; van der Tempel et al, 2016). Additionally, Daniulaityte et al, (2015) identified a greater prevalence of dabbing-related tweets among states that allowed recreational and/or medicinal marijuana use versus states where use is still illegal; this study is informative for potential surveillance of dabbing.…”
Section: Introductionmentioning
confidence: 99%